1990
DOI: 10.1111/j.1464-5491.1990.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction and Silent Myocardial Ischaemia on Exercise Testing in Diabetes Mellitus

Abstract: The incidence and mechanism of painless myocardial ischaemia on exercise testing in diabetic patients is not clear. Therefore, two studies were performed. Retrospectively, all exercise tests carried out in our hospital during the past 5 years were reviewed for silent ischaemia. Prospectively, diabetic patients with known or suspected coronary artery disease underwent autonomic function testing and a second exercise test. Of 1653 exercise tests reviewed, 247 were positive (ST depression greater than 0.1 mV). Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…In diabetic patients, the physiological dilation of whole coronary circulation is impaired, which may cause silent episodes of myocardial hypoxia during current life episodes that activate the sympathetic nervous system, such as exercise, mental stress, or cold exposure. Episodes of myocardial ischemia, which are more frequently observed in diabetic patients than in the other patients because of diabetic neuropathy (49,50), might progressively deteriorate the myocardium and lead to diabetic myocardiopathy, even in patients without coronary artery stenosis (3)(4)(5). As DFX has been demonstarted to restore coronary epicardial (13) and microcirculation vasomotion in diabetic patients without any other coronary risk factors, antioxidant therapy might be beneficial for long-term preservation of myocardial perfusion and heart function.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, the physiological dilation of whole coronary circulation is impaired, which may cause silent episodes of myocardial hypoxia during current life episodes that activate the sympathetic nervous system, such as exercise, mental stress, or cold exposure. Episodes of myocardial ischemia, which are more frequently observed in diabetic patients than in the other patients because of diabetic neuropathy (49,50), might progressively deteriorate the myocardium and lead to diabetic myocardiopathy, even in patients without coronary artery stenosis (3)(4)(5). As DFX has been demonstarted to restore coronary epicardial (13) and microcirculation vasomotion in diabetic patients without any other coronary risk factors, antioxidant therapy might be beneficial for long-term preservation of myocardial perfusion and heart function.…”
Section: Discussionmentioning
confidence: 99%
“…One study 6 found that 29% diabetes who were asymptomatic for CAD had SMI on 24 hour ambulatory monitoring exercise electrocardiogram.Another similar study 7 had shown higher predominance of SMI in DM as compared to non diabetics. Another study 8 in India identified that 38.3% of DM beyond prior CAD had SMI on treadmill test.Another study 8 from India, reported 50% incidence of silent myocardial ischemia in diabetics on exercise electrocardiogram and 35% on ambulatory monitoring.Yet another group 9 found 12.1% of diabetics free of CAD to have SMI on exercise electrocardiogram testing.Another study 10 , found that SMI was positive in 14(46.7%) out of 30 DM patients by treadmill test.One more study population 11 identified that a total of 113/522 patients (22%) had SMI using stress testing in asymptomatic patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…There are at least three studies which have shown that silent ischaemia is more prevalent in patients with autonomic neuropathy than in those with normal autonomic function [17,59,60] and two of these [59,60] show that the proportion of ischaemic episodes that are silent is higher in patients with autonomic neuropathy. Additional support for an association between autonomic neuropathy and silent myocardial ischaemia is provided by two studies [47,48] that found diabetic patients experienced chest pain later after the onset of ST depression than non-diabetic patients and this delay was related to impairment in the tests of autonomic nervous function.…”
Section: Association Of Diabetic Autonomic Neuropathy With Silent Myomentioning
confidence: 99%